A Study Looking at the Teaching of Peripheral Arterial Disease to Medical Personnel in Nepal: How well are we doing and how might we be able to improve? - Krueger, E.; Karmacharya, R. M.; Klinger, D. (Kathmandu University Medical Journal, 2021)
Background There is currently no data showing the prevalence of peripheral arterial disease in Nepal, although they have a high incidence of risk factors in their population such as diabetes, hypertension, and high volume of smoke inhalation. Objective To quantify a gap in medical education curriculum in Nepal as it pertains to medical trainees that have a lack of exposure to peripheral arterial disease (PAD) in a clinical setting as well as improve lecture quality on peripheral arterial disease. Method A survey was sent out to 615 medical trainees in Nepal with a survey completion rate of 44%. The results indicate that both medical students and intern doctors feel most confident in their ability to diagnose peripheral arterial disease and comfortable ordering a workup for peripheral arterial disease when their education includes both a dedicated lecture and care of a patient. Result The self-reported ability to diagnose peripheral arterial disease increased in medical students from 21.9% in the lecture only group to 44.4% in the group who had both lecture and cared for a patient. The current curriculum at the Kathmandu University School of Medical Sciences only allows two hours in the medical school to cover all vascular topics and is taught with a traditional PowerPoint method. Conclusion To improve this area of curriculum, we recommend increasing the allotted time for lectures as well as demonstrate on live patients the evaluation for peripheral arterial disease.